Program Kelas Ibu Hamil Sebagai Upaya Pencegahan Komplikasi Kehamilan Di Puskesmas Sokaraja II - Ikhwah Mu'minah; Atika Nur Azizah (INVOLUSI: Jurnal Ilmu Kebidanan, 2021)
According to Law No. 36 of 2009 on health, one of the efforts to improve maternal health aims to maintain the health of mothers and children and reduce maternal mortality. The government's efforts to achieve this goal are to improve midwifery services and disseminate health of both mother and childbooks. One of the efforts to provide midwifery services is a class for pregnant women. Pregnant mothers class is a means of learning together about health for pregnant women in the form of face-to-face groups which aims to increase the knowledge and skills of mothers regarding pregnancy, childbirth, postpartum care, baby care, infectious diseases. In qualitative research with a phenomenological descriptive approach. The results of the study can be concluded that the participation of pregnant women in the class of pregnant women is strongly influenced by factors of education, knowledge and work. The occupational factor is the biggest obstacle for pregnant women where mothers who work as laborers rarely attend pregnant women classes because the schedule for carrying out classes for pregnant women and working schedules is not appropriate.